Horizontal transverse electrolytic tank device for preparing CO through large-area electrocatalytic reduction of carbon dioxide and application of electrolytic tank device
By using transverse structure, nylon microporous separator and double-layer cathode catalyst in the electrolytic cell, the problems of uneven temperature, low utilization and short life of the electrolytic cell under large-area electrode conditions are solved, and an efficient and stable CO2 electrocatalytic reduction process is achieved.
Patent Information
- Application Number
- CN202411684074.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electrolytic cells have problems such as uneven reaction temperature, increased overpotential, increased hydrogen evolution reaction, low CO2 utilization rate and short service life under large-area electrode conditions. The ion exchange membrane is prone to degradation in a highly alkaline environment and has reduced mechanical strength, which limits the size and life of the electrolytic cells.
The transverse electrolytic cell structure is used to increase the runner width, promote the uniform flow of electrolyte and O2 desorption and discharge; use nylon microporous separators to replace the traditional anion exchange membrane to improve material transferability and battery performance; design a new cavity runner structure and a double-layer cathode catalyst structure to improve catalytic efficiency and CO2 utilization.
It realizes stable operation of large-area electrodes under high current conditions, improves catalytic efficiency and CO2 utilization, extends the service life of the electrolytic cell, and reduces production costs.
Smart Images

Figure CN119876976A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy utilization devices, and more specifically to a horizontally placed large-area electrolytic cell device for preparing CO by electrocatalytic reduction of CO2 and its application. Background Art
[0002] In recent years, with the increase of population and the expansion of industrialization, people's demand for energy has gradually increased. At present, the main source of about 80% of energy is the combustion of fossil fuels, which will inevitably lead to excessive emissions of CO2 and aggravate the greenhouse effect. How to effectively treat it and control its emissions has become a hot research field. It is a promising method to convert CO2 back into fuel or industrial raw materials (CO, methane, ethylene, methanol, ethanol, formate, formaldehyde, etc.) through the electrochemical reduction reaction process. Compared with other CO2 utilization technologies, it has higher industrialization potential due to its high reaction rate, good carbon dioxide conversion rate and the use of renewable electricity. However, compared with water electrolysis technology, the industrial electrocatalytic reduction of CO2 is still in its infancy. Among the various CO2 electroreduction products, the production of CO can achieve a significant selectivity of nearly 100% (Faraday efficiency), so there are many studies on the efficient electrocatalytic reduction of CO2 to CO. At present, the zero-gap electrolyzer combining the technical characteristics of gas diffusion electrode and membrane electrode assembly structure has gradually become the first choice. While maintaining high CO2 reduction selectivity, it also effectively reduces the amount of electrolyte and ohmic resistance, and reaches the industrial current density standard (>200mA / cm 2 ).
[0003] However, when the electrode area increases, it will lead to uneven reaction temperature, increased overpotential, and aggravated hydrogen evolution reaction. In addition, in the alkaline electrolyte solution (KOH or KHCO3) and the traditional single-layer cathode catalyst structure, CO2 is easy to combine with the electrolyte solution and produce precipitation, which greatly reduces the utilization rate of CO2 and greatly shortens the service life of the electrolytic cell. Therefore, the long-term stability of the electrolytic cell is poor, and it is an urgent problem to be solved that large-area electrodes cannot be used for production. At present, most CO2RR electrolytic cells use ion exchange membranes to increase the ion transfer rate and enhance mass transfer. However, while these ion exchange membranes have high ion conduction rates, they are more likely to absorb water and produce swelling, resulting in poor material stability and reduced mechanical strength, which still limits the life and size of the electrolytic cell. Further, taking modification or reinforcement measures for these ion exchange membranes will increase technical requirements and costs. In addition, with the increase of the reaction area of the electrolytic cell, the output of gas products, such as O2, will also increase significantly, which will lead to coverage of the catalytic area and hinder the flow of electrolytes, seriously hindering the mass transfer process and greatly reducing the catalytic efficiency. Therefore, the development of a device for electrolytic reduction of CO2 to produce CO that can be produced on a large scale at a high total current with stable Faraday efficiency and long service life will hopefully be used on a large scale, opening the door to new areas of energy conversion. Summary of the invention
[0004] The present invention overcomes the deficiencies in the prior art and provides a horizontally placed large-area electrocatalytic reduction of CO2 to prepare CO and its application, aiming to increase the width of the flow channel by adopting a horizontal electrolytic cell structure (the electrolytic cell electrodes are parallel to the ground), accelerate the desorption and discharge of anode O2, and thus increase the catalytic area of the anode and improve the catalytic efficiency. At the same time, in order to match the high catalytic efficiency of the electrolytic cell, a nylon microporous diaphragm is used to enhance the material transfer of the electrolytic cell, reduce the voltage of the electrolytic cell, and solve the problem that traditional anion exchange membranes are easily degraded in strong alkaline electrolytes, thereby improving the performance and service life of the electrolytic cell. A new cavity flow channel structure under the horizontal structure is adopted to further promote the uniform flow of electrolytes and the discharge of O2. Finally, a double-layer cathode catalyst structure is adopted to improve the conversion efficiency and utilization rate of CO2.
[0005] The purpose of the present invention is achieved through the following technical solutions.
[0006] A horizontally placed large-area electrocatalytic reduction electrolytic cell device for preparing CO by CO2 production includes an anode cover, an anode flow channel assembly, an anode, a microporous diaphragm, an Ag catalyst layer, a cathode and a cathode flow channel assembly.
[0007] The anode cover, anode flow channel assembly, anode, microporous diaphragm, cathode and cathode flow channel assembly are arranged in sequence from top to bottom and are connected by fixing screws and nuts. Insulating tape is wrapped on the outside of the fixing screws. The bottom surface of the anode cover adopts a concave structure. A cavity structure is formed between the anode cover and the anode flow channel assembly to provide an additional diffusion path for O2. An O2 discharge hole is opened on the anode cover. A serpentine anode flow channel with an inverted S-shaped groove is formed on the anode flow channel assembly. A serpentine cathode flow channel with an S-shaped groove is formed on the cathode flow channel assembly. The anode flow channel is used to pass an electrolyte solution, and the electrolyte solution is in contact with the cavity structure and the anode respectively. The cathode flow channel is used to pass a cathode reactant, and the cathode reactant is only in contact with the cathode. The anode flow channel assembly and the cathode flow channel assembly are respectively connected to the positive and negative electrodes of an external power supply. The Ag catalyst layer is coated on the bottom surface of the microporous diaphragm and the surface of the cathode respectively.
[0008] The electrolyte solution is 1M KOH solution, the inlet of the anode flow channel is connected to the inlet of the electrolyte solution delivery system, the outlet of the anode flow channel is connected to the outlet of the electrolyte solution delivery system, and the flow rate of the electrolyte solution is 800-1000mL / min, preferably 900mL / min.
[0009] The electrolyte solution delivery system includes an electrolyte storage tank, a liquid delivery device, an input pipeline and an output pipeline. The outlet of the electrolyte storage tank is connected to the inlet of the anode flow channel through the input pipeline. The liquid delivery device is arranged on the input pipeline. The inlet of the electrolyte storage tank is connected to the outlet of the anode flow channel through the output pipeline. The liquid delivery device adopts a diaphragm pump.
[0010] The cathode reactant is CO2 gas, the inlet of the cathode flow channel is connected to the CO2 storage tank through a gas input pipeline, and a mass flow controller is arranged on the input pipeline for controlling the flow rate of CO2 gas flowing into the cathode flow channel. The outlet of the cathode flow channel is connected to a spherical CaSO4 solid dehumidification device, a mass flow indicator and a CO2, CO mixed storage tank in sequence through a gas output pipeline, and the mass flow indicator is used to measure the flow rate of the CO2 and CO mixed gas at the outlet of the cathode flow channel. The CO2, CO mixed storage tank is connected to a gas chromatograph for online quantitative measurement of the gas product components at the outlet of the cathode flow channel.
[0011] The anode cover, the anode flow channel assembly and the cathode flow channel assembly are made of stainless steel.
[0012] The anode adopts a material structure composed of iridium oxide / titanium mesh.
[0013] The cathode is made of carbon paper.
[0014] The microporous membrane is made of nylon material, the thickness of the microporous membrane is 35-40 μm, preferably 38 μm, and the pore size of the microporous membrane is 0.40-0.50 μm, preferably 0.45 μm.
[0015] The current density of the external power supply is 25-200 mA / cm 2 , preferably 25, 50, 100, 150, 200 mA / cm 2 .
[0016] The anode cover, the anode flow channel assembly, the anode, the cathode and the cathode flow channel assembly are fixed with nitrile rubber gaskets.
[0017] The Ag catalyst layer is coated on the bottom surface of the microporous membrane and the surface of the cathode by spraying to greatly increase the catalytic area. The process of the spraying method is as follows: first, weigh the mass of the microporous membrane and the cathode, disperse 65 mg of Ag nanoparticles in 8 mL of isopropanol aqueous solution to prepare Ag catalyst ink, and then ultrasonically treat for 1 hour. By using an electric sprayer, the above-mentioned Ag catalyst ink is sprayed on the bottom surface of the microporous membrane and the surface of the cathode respectively and evenly. Finally, a hot plate and infrared light are used to accelerate the drying of the Ag catalyst ink sprayed on the bottom surface of the microporous membrane and the surface of the cathode, and the mass of the microporous membrane and the electrode is weighed again. Repeat the above process until the weight gain of the microporous membrane and the cathode reaches 1 mg / cm 2 until.
[0018] Application of a horizontally placed large-area electrolytic cell device for producing CO by electrocatalytic reduction of CO2 in the electrocatalytic reduction of CO2 gas.
[0019] The beneficial effects of the present invention are as follows: the present invention promotes the uniform flow of electrolytes by adopting a horizontal electrolytic cell structure, accelerates the mass transfer process on the electrode surface, and uniformly distributes the reaction temperature;
[0020] The use of nylon microporous diaphragm can not only meet the requirements of the horizontal electrolytic cell for high mass transfer rate, but also effectively reduce the mass transfer distance and resistance of the electrolyte. At the same time, it also ensures that the diaphragm material has a stable structure and performance, prolongs the service life of the electrolytic cell, and reduces production costs;
[0021] The anode flow channel structure of the electrolytic cell has been redesigned to make the electrolyte flow more uniform, reduce the electrolyte "dead zone" in the flow channel, and promote the discharge of O2 along with the electrolyte. At the same time, a cavity is reserved above the anode flow channel, so that the O2 generated in the anode electrolyte flow channel can diffuse into the air at the same time, further promoting the discharge of O2. This effectively reduces the problems of reduced reaction area and decreased material transfer efficiency caused by the attachment of O2 to the anode surface;
[0022] In addition, the double-layer catalyst structure on the cathode electrode surface effectively prevents the diffusion of CO2 from the cathode surface into the electrolyte solution and greatly increases the electrode reaction area, effectively improving the utilization rate of CO2 gas reactants and greatly alleviating the reduction of Faraday efficiency during the use of the electrolytic cell;
[0023] Finally, based on the above points, the electrode area of the electrolytic cell can be enlarged to 100 cm under high current conditions. 2 , while still maintaining good catalytic efficiency and a long service life, making it possible to produce and apply electrolytic cell devices for the electrocatalytic reduction of CO2 to produce CO with a large catalytic area. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of the structure of an electrolytic cell device for preparing CO by electrolytic reduction of CO2 according to the present invention;
[0025] In the figure, 1 is an anode cover, 2 is an anode flow channel assembly, 3 is an electrolyte solution, 4 is an anode, 5 is a microporous diaphragm, 6 is an Ag catalyst layer, 7 is a cathode, 8 is a cathode flow channel assembly, 9 is a fixing screw, and 10 is a nut;
[0026] Figure 2 for Figure 1 Schematic diagram of the structure of the anode cover;
[0027] Figure 3 for Figure 1 A schematic diagram of the structure of the anode flow channel assembly;
[0028] Figure 4 for Figure 1 A schematic diagram of the structure of the middle cathode flow channel assembly;
[0029] Figure 5 The images of the changes in the cell voltage, CO and H2 Faraday efficiency of the double-layer cathode catalyst electrolyzer at different current densities;
[0030] Figure 6 The images of the changes in the cell voltage, CO and H2 Faraday efficiency of the single-layer cathode catalyst electrolyzer at different current densities;
[0031] Figure 7 For a double-layer cathode catalyst electrolytic cell at 200mA / cm 2 The image of the change in the electrolytic cell voltage, CO and H2 Faraday efficiency after continuous operation for 100 hours at a current density of . DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through specific embodiments.
[0033] like Figure 1 As shown, a horizontally placed large-area electrocatalytic reduction electrolytic cell device for preparing CO by CO2 production includes an anode cover 1, an anode flow channel assembly 2, an anode 4, a microporous diaphragm 5, an Ag catalyst layer 6, a cathode 7 and a cathode flow channel assembly 8.
[0034] The anode cover 1, the anode flow channel assembly 2, the anode 4, the microporous diaphragm 5, the cathode 7 and the cathode flow channel assembly 8 are arranged in sequence from top to bottom and are connected by fixing screws 9 and nuts 10. The outer side of the fixing screws 9 is wrapped with insulating tape. The bottom surface of the anode cover 1 adopts a concave structure, and a cavity structure is formed between the anode cover 1 and the anode flow channel assembly 2 to provide an additional diffusion path for O2. An O2 discharge hole is opened on the anode cover 1, and a serpentine anode flow channel with an inverted S-shaped groove is formed on the anode flow channel assembly 2. A serpentine cathode flow channel with an S-shaped groove is formed on the cathode flow channel assembly 8. The anode flow channel is used to pass an electrolyte solution 3, and the electrolyte solution 3 is in contact with the cavity structure and the anode 4 respectively. The cathode flow channel is used to pass a cathode reactant, and the cathode reactant is only in contact with the cathode 7. The anode flow channel assembly 2 and the cathode flow channel assembly 8 are respectively connected to the positive and negative electrodes of an external power supply. Ag catalyst layers 6 are coated on the bottom surface of the microporous diaphragm 5 and the surface of the cathode 7, respectively.
[0035] The anode flow channel and cathode flow channel adopt a new type of horizontal structure. Vertical flow channels are not suitable for increasing the flow channel width. When a wide serpentine flow channel is used, the energy required to drive the electrolyte flow increases significantly. At the same time, the wide vertical flow channel structure is more likely to cause uneven flow of the electrolyte. In addition, in the process of the electrolyte flowing to a lower place, the O2 in this part of the pipeline is more difficult to discharge due to buoyancy problems. Therefore, the electrolytic cell adopts a horizontal structure to increase the flow channel width, increase the electrolyte flow rate, reduce the electrolyte flow resistance, and thus reduce the electrolyte flow "dead zone" in the flow channel, accelerate the desorption of O2 generated on the anode surface, increase the anode catalytic area, and improve the catalytic efficiency. The anode cover 1 and the anode flow channel assembly 2 together form a horizontal flow channel structure with a cavity. The cavity above the horizontal flow channel structure provides an additional diffusion path for O2, which accelerates the discharge rate of O2 in the flow channel.
[0036] The electrolyte solution 3 uses 1M KOH solution, the inlet of the anode flow channel is connected to the inlet of the electrolyte solution delivery system, the outlet of the anode flow channel is connected to the outlet of the electrolyte solution delivery system, and the flow rate of the electrolyte solution 3 is 800-1000mL / min, preferably 900mL / min.
[0037] The electrolyte solution delivery system includes an electrolyte storage tank, a liquid delivery device, an input pipeline and an output pipeline. The outlet of the electrolyte storage tank is connected to the inlet of the anode flow channel through the input pipeline. The liquid delivery device is arranged on the input pipeline. The inlet of the electrolyte storage tank is connected to the outlet of the anode flow channel through the output pipeline. The liquid delivery device adopts a diaphragm pump.
[0038] The cathode reactant is CO2 gas, and the inlet of the cathode flow channel is connected to the CO2 storage tank through a gas input pipeline. A mass flow controller is provided on the input pipeline to control the flow rate of CO2 gas flowing into the cathode flow channel. The outlet of the cathode flow channel is connected to a spherical CaSO4 solid dehumidification device, a mass flow indicator and a CO2, CO mixed storage tank in sequence through a gas output pipeline. The mass flow indicator is used to measure the flow rate of the CO2 and CO mixed gas at the outlet of the cathode flow channel. The CO2, CO mixed storage tank is connected to a gas chromatograph for online quantitative measurement of the gas product components at the outlet of the cathode flow channel.
[0039] The anode cover 1, the anode flow channel assembly 2 and the cathode flow channel assembly 8 are made of stainless steel.
[0040] The anode 4 is made of iridium oxide / titanium mesh.
[0041] The cathode 7 is made of carbon paper.
[0042] The microporous membrane 5 is made of nylon, the thickness of the microporous membrane 5 is 38 μm, and the pore size of the microporous membrane 5 is 0.45 μm.
[0043] Nylon microporous membrane 4 is used to replace anion exchange membrane or bipolar membrane. Anion exchange membrane will produce affinity substitution and other reactions in strong alkaline electrolytes, which will cause the main chain structure or cationic group to decompose, causing the anion exchange membrane to lose its ion transfer ability and reduce its mechanical properties. The nylon microporous membrane 4 has excellent alkali resistance, which can improve the stability of the membrane material in high alkaline electrolytes and increase the stable operation time of the reactor. The mass transfer process of anion exchange membrane and bipolar membrane is complicated, which greatly increases the internal resistance of the electrolytic cell. The mass transfer driving force of nylon microporous membrane 4 depends on the concentration difference on both sides of the membrane and the mass transfer process is simple and rapid. Therefore, the use of nylon microporous membrane 4 can improve the material transfer efficiency of the reactor and reduce the internal resistance. Finally, the cost of nylon microporous membrane 4 is much lower than that of anion exchange membrane and bipolar membrane. The effective reaction area of anode 4, microporous membrane 5 and cathode 7 is 100cm 2 .
[0044] The current density of the external power supply is 25-200mA / cm 2 , preferably 25, 50, 100, 150, 200 mA / cm 2 .
[0045] The anode cover 1, the anode flow channel assembly 2, the anode 4, the cathode 7 and the cathode flow channel assembly 8 are fixed by using nitrile rubber gaskets.
[0046] The Ag catalyst layer 6 is coated on the bottom surface of the microporous membrane 5 and the surface of the cathode 7 by spraying to greatly increase the catalytic area. The process of the spraying method is as follows: first, the mass of the microporous membrane 5 and the cathode 7 is weighed, 65 mg of Ag nanoparticles are dispersed in 8 mL of isopropanol aqueous solution to prepare Ag catalyst ink, and then ultrasonically treated for 1 hour. By using an electric sprayer, the above-mentioned Ag catalyst ink is sprayed on the bottom surface of the microporous membrane 5 and the surface of the cathode 7 respectively and evenly. Finally, a hot plate and infrared light are used to accelerate the drying of the Ag catalyst ink sprayed on the bottom surface of the microporous membrane 5 and the surface of the cathode 7. The above process is repeated until the weight gain of the microporous membrane 5 and the cathode 7 reaches 1 mg / cm 2 until.
[0047] The double-layer cathode catalyst structure of the present invention can effectively increase the CO2 catalytic rate, thereby reducing the CO2 and OH in the electrolyte. - In addition, if only the Ag catalyst layer is sprayed onto the cathode surface, it is a single-layer cathode catalyst electrolytic cell.
[0048] test:
[0049] The anode cover 1, anode flow channel assembly 2 and cathode flow channel assembly 8 of the electrolytic cell are all made of 304 stainless steel. The size of the anode cover 1 is 150mm×150mm×25.0mm (length×width×thickness). The anode cover 1, anode flow channel assembly 2 and cathode flow channel assembly 8 are evenly distributed with 8 M6 fixing screw holes for fastening, and the fixing screws 9 are wrapped with insulating tape for insulation between the positive and negative stages. There is a countersunk hole with a diameter of 9.6mm at the top of the anode cover 1 for anode gas discharge (i.e. oxygen). In addition, the anode cover 1 contains a square chamber of 100.0mm×100.0mm×20.0mm (length×width×depth) and is connected to the countersunk hole. The anode flow channel assembly 2 and the cathode flow channel assembly 8 are composed of an active area of approximately 100cm 2The anode flow channel 2 is composed of a single-channel serpentine flow channel. The flow channel depth of the anode flow channel 2 is 40.0mm, and the cathode flow channel 8 is 15mm deep. The anode flow channel 2 and the cathode flow channel 8 are both provided with threaded holes with a diameter of 9.6mm at both ends of the serpentine flow channel to connect the hose and pass the reactant. Among them, the center of the threaded hole of the anode flow channel assembly 2 is 8mm away from the edge of one side and 32mm away from the other side. The center of the threaded hole of the cathode flow channel assembly 8 is 7.5mm away from the side edge of the flow channel. The anode flow channel assembly 2 and the cathode flow channel assembly 8 are both provided with a 1mm thick steel sheet for easy disassembly. The ridge width of the anode flow channel assembly 2 and the cathode flow channel assembly 8 is 2.5mm, and the width of the anode flow channel and the cathode flow channel is 15mm. The corners of the anode cover 1, the anode flow channel assembly 2 and the cathode flow channel assembly 8 are designed with rounded corners to increase the flow stability of the electrolyte solution 3 and reduce the flow "dead zone". The "sandwich" shaped extrusion sealing structure composed of the anode 4, the nylon microporous diaphragm 5 and the cathode 7 has a size of 120.0 mm × 120.0 mm (length × width), and the size of the nylon microporous diaphragm 5 is 130.0 mm × 130.0 mm (length × width). In addition, the nylon microporous diaphragm 5, the anode 4 and the cathode 7 are fixed by extrusion with two 0.4 mm thick nitrile rubber pads. The center of the nitrile rubber pad is cut to the same size as the anode flow channel assembly 2 and the cathode flow channel assembly 8. The anode 4 and the cathode 7 are connected to the terminal through a double-sided conductive copper tape. During assembly, the cathode flow channel assembly 8, the nitrile rubber pad, the cathode 7, the nylon microporous diaphragm 5, the anode 4, the nitrile rubber pad, the anode flow channel assembly 2, the nitrile rubber pad and the anode cover 1 are assembled in order from bottom to top, and fixed with eight screws 9 and nuts 10. Use a torque wrench to gradually tighten the screws to 4.0-6.0 Nm, so that the carbon paper compression rate is 20%-25%, and the assembly is completed.
[0050] Before the test, a 1M KOH electrolyte solution 3 with a flow rate of 900 mL / min was continuously introduced into the inlet of the anode flow channel assembly 2 for 5 minutes to fill the electrolytic cell with electrolyte and maintain a stable flow, and the electrolyte was continuously introduced during the reaction. A mass flow controller was used to stably introduce 200 sccm of CO2 gas into the inlet of the cathode flow channel assembly 8 1 minute in advance.
[0051] During the test, the electrochemical workstation continuously and stably applied 25, 50, 100, 150 and 200 mA / cm 2 The positive electrode of the workstation is connected to the conductive copper tape of the anode 4 of the electrolytic cell as the counter electrode, and the negative electrode is connected to the conductive copper tape of the cathode 7 of the electrolytic cell as the working electrode, and the voltage change is monitored in real time. After the reaction is stable, the outlet of the cathode flow channel assembly 8 is connected to the spherical CaSO4 solid for dehumidification and then flows through the mass flow indicator to detect the volume flow, pressure and temperature, and then flows into a gas collection bottle, and then connected to the gas chromatograph to analyze the gas product composition at the outlet to calculate the Faraday efficiency.
[0052] Stability test:
[0053] The reactor was assembled as before.
[0054] Before the test, a 1M KOH electrolyte solution 3 with a flow rate of 900 mL / min was continuously introduced into the inlet of the anode flow channel assembly 2 for 5 minutes to fill the electrolytic cell with electrolyte and maintain a stable flow, and the electrolyte was continuously introduced during the reaction. A mass flow controller was used to stably introduce 200 sccm of CO2 gas into the inlet of the cathode flow channel assembly 8 1 minute in advance.
[0055] During the test, the electrochemical workstation continuously and stably applied 25, 50, 100, 150 and 200 mA / cm 2 The positive electrode of the workstation is connected to the conductive copper tape of the anode 4 of the electrolytic cell as the counter electrode, and the negative electrode is connected to the conductive copper tape of the cathode 7 of the electrolytic cell as the working electrode, and the voltage change is monitored in real time. After the reaction is stable, the outlet of the cathode flow channel assembly 8 is connected to the spherical CaSO4 solid for dehumidification and then flows through the mass flow indicator to detect the volume flow, pressure and temperature, and then flows into a gas collection bottle, and then connected to the gas chromatograph and recorded every 10 hours or so, and the gas product composition at the outlet is analyzed to calculate the Faraday efficiency.
[0056] Gas phase product detection and analysis:
[0057] For gaseous products, the gas at the outlet of the cathode flow channel assembly 8 of the electrolytic cell is dried by spherical CaSO4 and then passed into a mass flow indicator to preliminarily measure the volume flow of the gas. At the same time, important information such as the pressure and temperature of the gas is obtained to determine the smooth operation of the reactor. Subsequently, the gaseous products enter the gas collecting bottle and are collected and quantitatively detected online using gas chromatography. After obtaining the gas composition, the outlet gas volume flow is recalibrated and calculated based on the gas composition, temperature, and pressure data.
[0058] Evidence of relevant effects of the embodiments. The embodiments of the present invention have achieved some positive effects during the development or use process, and indeed have great advantages over the prior art. The following content is described in conjunction with the data, charts, etc. of the test process.
[0059] Figure 5 The figure is a graph showing the change in cell voltage, CO and H2 Faraday efficiency of a double-layer cathode catalyst electrolytic cell at different current densities provided by the present invention. 2 When the current density gradually increases to 200 mA / cm 2, the CO Faradaic efficiency of the double-layer cathode catalyst electrolyzer was still as high as 92.6%, and the electrolyzer voltage increased slightly to 2.75V.
[0060] Figure 6 The graphs of the cell voltage, CO and H2 Faraday efficiency changes of the single-layer cathode catalyst electrolytic cell at different current densities provided by the present invention are shown in Figure 2. 2 When the single-layer cathode catalyst electrolyzer has a CO Faraday efficiency of 97%, the electrolyzer voltage is only 2.45 V. As the current density gradually increases to 100 mA / cm 2 , the CO Faraday efficiency of the single-layer cathode catalyst electrolyzer can still be maintained at about 80%. When the current density continues to increase to 200mA / cm 2 When the CO Faraday efficiency was drastically reduced to 62%, the cell voltage rose to 3.37 V, indicating that the cell could not continue to operate normally.
[0061] The main reasons are as follows: 1. The new electrolyte flow channel effectively improves the desorption and discharge rate of anode O2. The nylon microporous diaphragm effectively improves the mass transfer efficiency and operation time of the electrolytic cell. These improvements have successfully scaled up the single-layer cathode catalyst electrolytic cell to 100 cm 2 And it can operate stably within a certain current density range. 2. Further increase the double-layer cathode catalyst structure to improve the cathode catalytic efficiency of the electrolytic cell, and greatly improve the CO2 catalytic efficiency. - The amount of binding is reduced, and the subsequent salt precipitation phenomenon is weakened. This allows the double-layer cathode catalyst electrolyzer to be able to 2 Continuously operate at a current density of .
[0062] Figure 7 It is a double-layer cathode catalyst electrolytic cell at 200mA / cm 2 The CO Faraday efficiency and voltage change curves over time at a current density of . At the beginning of the reaction, the CO Faraday efficiency of the reactor was about 96% and the voltage was 2.3V. After 100 hours of continuous reaction, the CO Faraday efficiency decreased to about 92%, and the voltage increased to about 2.8-3V and remained stable. This shows that at high current density, the double-layer cathode catalyst electrolyzer has good stability.
[0063] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A horizontally placed large-area electrolytic cell device for producing CO by electrocatalytic reduction of carbon dioxide, characterized in that: It includes an anode cover, an anode flow channel assembly, an anode, a microporous diaphragm, an Ag catalyst layer, a cathode and a cathode flow channel assembly. The anode cover, anode flow channel assembly, anode, microporous diaphragm, cathode and cathode flow channel assembly are arranged in sequence from top to bottom and are connected by fixing screws and nuts. Insulating tape is wrapped on the outside of the fixing screws. The bottom surface of the anode cover adopts a concave structure. A cavity structure is formed between the anode cover and the anode flow channel assembly to provide an additional diffusion path for O2. An O2 discharge hole is opened on the anode cover. A serpentine anode flow channel with an inverted S-shaped groove is formed on the anode flow channel assembly. A serpentine cathode flow channel with an S-shaped groove is formed on the cathode flow channel assembly. The anode flow channel is used to pass an electrolyte solution, and the electrolyte solution is in contact with the cavity structure and the anode respectively. The cathode flow channel is used to pass a cathode reactant, and the cathode reactant is only in contact with the cathode. The anode flow channel assembly and the cathode flow channel assembly are respectively connected to the positive and negative electrodes of an external power supply. The Ag catalyst layer is coated on the bottom surface of the microporous diaphragm and the surface of the cathode respectively.
2. The horizontally placed large-area electrocatalytic reduction electrolytic cell device for preparing CO by carbon dioxide according to claim 1 is characterized in that: The electrolyte solution is 1M KOH solution, the inlet of the anode flow channel is connected to the inlet of the electrolyte solution delivery system, the outlet of the anode flow channel is connected to the outlet of the electrolyte solution delivery system, and the flow rate of the electrolyte solution is 800-1000mL / min, preferably 900mL / min.
3. The electrolytic cell device for preparing CO by electrocatalytic reduction of carbon dioxide over a large area horizontally placed according to claim 1 is characterized in that: The electrolyte solution delivery system includes an electrolyte storage tank, a liquid delivery device, an input pipeline and an output pipeline. The outlet of the electrolyte storage tank is connected to the inlet of the anode flow channel through the input pipeline. The liquid delivery device is arranged on the input pipeline. The inlet of the electrolyte storage tank is connected to the outlet of the anode flow channel through the output pipeline. The liquid delivery device adopts a diaphragm pump.
4. The electrolytic cell device for preparing CO by electrocatalytic reduction of carbon dioxide over a large area horizontally placed according to claim 1 is characterized in that: The cathode reactant is CO2 gas, the inlet of the cathode flow channel is connected to the CO2 storage tank through a gas input pipeline, and a mass flow controller is arranged on the input pipeline for controlling the flow rate of CO2 gas flowing into the cathode flow channel. The outlet of the cathode flow channel is connected to a spherical CaSO4 solid dehumidification device, a mass flow indicator and a CO2, CO mixed storage tank in sequence through a gas output pipeline, and the mass flow indicator is used to measure the flow rate of the CO2 and CO mixed gas at the outlet of the cathode flow channel. The CO2, CO mixed storage tank is connected to a gas chromatograph for online quantitative measurement of the gas product components at the outlet of the cathode flow channel.
5. The horizontally placed large-area electrocatalytic reduction electrolytic cell device for producing CO according to claim 1 is characterized in that: The anode cover, the anode flow channel assembly and the cathode flow channel assembly are made of stainless steel; the anode is made of a material structure composed of iridium oxide / titanium mesh; and the cathode is made of a carbon paper material structure.
6. The horizontally placed large-area electrocatalytic reduction electrolytic cell device for producing CO according to claim 1 is characterized in that: The microporous membrane is made of nylon material, the thickness of the microporous membrane is 35-40 μm, preferably 38 μm, and the pore size of the microporous membrane is 0.40-0.50 μm, preferably 0.45 μm.
7. The horizontally placed large-area electrocatalytic reduction electrolytic cell device for producing CO according to claim 1 is characterized in that: The current density of the external power supply is 25-200 mA / cm 2 , preferably 25, 50, 100, 150, 200 mA / cm 2 .
8. The horizontally placed large-area electrocatalytic reduction electrolytic cell device for producing CO according to claim 1 is characterized in that: The anode cover, the anode flow channel assembly, the anode, the cathode and the cathode flow channel assembly are fixed with nitrile rubber gaskets.
9. The horizontally placed large-area electrocatalytic reduction electrolytic cell device for producing CO according to claim 1 is characterized in that: The Ag catalyst layer is coated on the bottom surface of the microporous membrane and the surface of the cathode by spraying to greatly increase the catalytic area. The process of the spraying method is as follows: first, weigh the mass of the microporous membrane and the cathode, disperse 65 mg of Ag nanoparticles in 8 mL of isopropanol aqueous solution to prepare Ag catalyst ink, and then ultrasonically treat for 1 hour. By using an electric sprayer, the above-mentioned Ag catalyst ink is sprayed on the bottom surface of the microporous membrane and the surface of the cathode respectively and evenly. Finally, a hot plate and infrared light are used to accelerate the drying of the Ag catalyst ink sprayed on the bottom surface of the microporous membrane and the surface of the cathode, and the mass of the microporous membrane and the electrode is weighed again. Repeat the above process until the weight gain of the microporous membrane and the cathode reaches 1 mg / cm 2 until.
10. Use of the horizontally placed large-area electrolytic cell device for preparing CO by electrocatalytic reduction of carbon dioxide as claimed in any one of claims 1 to 9 in electrocatalytic reduction of CO2 gas, characterized in that: At a current density of 25 mA / cm 2 When the current density increases to 200 mA / cm 2 The CO Faraday efficiency of the electrolytic cell device was still as high as 92.6%, and the electrolytic cell voltage slightly increased to 2.75V; at 200mA / cm 2 At a current density of 1.5-2.0 V, the CO Faraday efficiency of the electrolytic cell device is 92-96% and the voltage is 2.3-3 V.